1995
DOI: 10.1017/s0033822200030642
|View full text |Cite
|
Sign up to set email alerts
|

Precision Calendar-Year Dating of the Elm Decline in a Sphagnum-Peat Bog in Southern Sweden

Abstract: ABSTRACT. The cause of the mid-Holocene elm decline in northwestern Europe and its relation to the contemporaneous transition from Mesolithic to Neolithic economy are still unclear, partly owing to the lack of a precise, calibrated chronology. Matching of a sequence of 14C dates to the calibration curve in combination with accurate 14C dating allows high-precision dating of paleoecological events. We have completed high-resolution dating of a Sphagnum-peat sequence from Agerods Mosse in southernmost Sweden. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…At Ageröd Mosse, Scania, Sweden, for example, the decline is dated to several decades around 3770 cal. BC (Skog and Regnéll, 1995) while at Bökebjerg, also in Scania around 40 km away, the decline is dated somewhat earlier, at ca. 3980 cal.…”
Section: The Floramentioning
confidence: 98%
“…At Ageröd Mosse, Scania, Sweden, for example, the decline is dated to several decades around 3770 cal. BC (Skog and Regnéll, 1995) while at Bökebjerg, also in Scania around 40 km away, the decline is dated somewhat earlier, at ca. 3980 cal.…”
Section: The Floramentioning
confidence: 98%
“…High-precision dating studies of the Ulmus decline have shown that at some sites the destruction of Ulmus populations occurred rapidly, over 2-3 decades (Peglar and Birks, 1993;Skog and Regnell, 1995). At the individual site scale, either intense human activity or a disease epidemic could have achieved this.…”
Section: Introductionmentioning
confidence: 99%
“…in southern Sweden (Skog and Regnéll 1995). It is hard to infer a precise timing for the elm decline in this study, but the time-depth curve (Fig.…”
Section: Pollen-inferred Vegetation Developmentmentioning
confidence: 82%